2011
DOI: 10.1007/s11433-011-4518-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on stress-strain behavior and constitutive model of hardfill material

Abstract: Hardfill is a new type of artificially cemented material for dam construction works, with a wide application prospect. Its mechanical behavior lies between concrete and rockfill materials. A series of large-scale triaxial tests are performed on hardfill specimens at different ages, and the stress-strain behavior of hardfill is further discussed. The strength and stress-strain relationship of hardfill materials show both frictional mechanism and cohesive mechanism. An age-related constitutive model of hardfill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…is is consistent with the observations of Fu et al [7] and other researchers [5] who have reported that increasing the cementing agent content is highly e ective in enhancing the shear strength of CSG and various other Advances in Materials Science and Engineering materials, such as cemented sand and polyurethane foam adhesive rock ll materials.…”
Section: Shear Strength Versus Cementing Agent Contentsupporting
confidence: 92%
See 4 more Smart Citations
“…is is consistent with the observations of Fu et al [7] and other researchers [5] who have reported that increasing the cementing agent content is highly e ective in enhancing the shear strength of CSG and various other Advances in Materials Science and Engineering materials, such as cemented sand and polyurethane foam adhesive rock ll materials.…”
Section: Shear Strength Versus Cementing Agent Contentsupporting
confidence: 92%
“…Crushed stone: particle sizes less than 5 mm (3%), 5-10 mm (20%), 10-20 mm (35%), and 20-40 mm (42%), sourced from a Nanjing suburb [5]. Sand: particle size of approximately 0-4.75 mm, mediumcoarse sand crushed from limestone.…”
Section: Materials Imentioning
confidence: 99%
See 3 more Smart Citations